The inside job : (and other skills I learned as a superspy) - Pearce, Jackson (Bloomsbury Childrens Books, 2016)
Together with his friends, twelve-year-old Hale, an overweight and non-athletic double agent against SRS, the corrupt spy organization he was raised in, travels to Switzerland to destroy the SRS bank account.